The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

State of the UK Climate in 2025 - Mike Kendon; Amy Doherty; Dan Hollis; Emily Carlisle; Stephen Packman; Nick Rayner; Ségolène Berthou; Lucy Barker; Steve Turner; Jamie Hannaford; Svetlana Jevrejeva; Andrew Matthews; et al. (International Journal of Climatology, 2026)

The ontogeny of foraging in meerkats, a cooperatively breeding mongoose - Chris Duncan; Zoe Turner; David Gaynor; Jack Thorley; Tim Vink; Tim Clutton-Brock (Animal Behaviour, 2025)

A case of Plasmodium falciparum malaria presenting 13 years after leaving an endemic area - David Hettle; Mustafa Elsayed; Samuel Mensah; Francesca Neuberger; Debbie Nolder; Hristina Vasileva; Kevin Tetteh; Tim Cutfield; Imogen Jones; Spencer Polley; Louise Turner; Thomas Lavstsen; et al. (Infectious Diseases, 2025)

Recognising and Protecting the National Benefit of Sustainable Fisheries in the UK - Sarah Coulthard; Ainsley Hatt; Phoebe Lewis; Bryce D. Stewart; Michael Roach; Robert Clark; Sam Fanshawe; Carole Sandrine White; Julie Urquhart; Jerry Percy; Tim Gray; Emily Bulled; et al. (Fish and Fisheries, 2025)
Sustainable commercial fishing makes valuable contributions to coastal regions and broader national benefits. This paper offers three arguments in relation to what is required for the societal benefits of sustainable fisheries to be fully realised and considers each in the context of the UK but with global relevance. First, there is a need to raise the profile of the full range of benefits that are delivered through sustainable fisheries to coastal communities and the broader public. In the UK, the delivery of a ‘national benefit’ objective through fisheries is now enshrined in law by the Fisheries Act, 2020; we operationalise this through a new framing that distils eight ‘national benefits’ that all sustainable fisheries should deliver. Second, better acknowledgement of what society gains from sustainable fisheries must be paralleled with recognition of what society is simultaneously at risk of losing through the decline of the fishing fleet. We detail this decline in a new analysis of long‐term UK data, which highlights that the decline is unequally felt, with some regions of the UK, and small‐scale fishing sectors, experiencing loss more acutely. This reality leads us to argue a third point, that if society is to retain and truly harness the benefits that flow from sustainable fisheries, governing bodies must act quickly to ensure that fisheries are environmentally sustainable, diverse and inclusive, pursuing fisheries that ‘leave no one behind’.

Biodiversity and environmental stressors along urban walking routes - Briony A. Norton; Meghann Mears; Philip H. Warren; Gavin M. Siriwardena; Kate E. Plummer; Tim Turner; Steven Hancock; Darren R. Grafius; Karl L. Evans (Urban Forestry & Urban Greening, 2023)

Global prevalence of setting longlines at dawn highlights bycatch risk for threatened albatross - David Kroodsma; Joanna Turner; Cian Luck; Tim Hochberg; Nathan Miller; Philip Augustyn; Stephanie Prince (Biological Conservation, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Temperature response of permafrost soil carbon is attenuated by mineral protection - Norman Gentsch; Birgit Wild; Robert Mikutta; Petr Čapek; Katka Diáková; Marion Schrumpf; Stephanie Turner; Cynthia Minnich; Frank Schaarschmidt; Olga Shibistova; Jörg Schnecker; Tim Urich; et al. (Global Change Biology, 2018)
Climate change in Arctic ecosystems fosters permafrost thaw and makes massive amounts of ancient soil organic carbon ( OC ) available to microbial breakdown. However, fractions of the organic matter ( OM ) may be protected from rapid decomposition by their association with minerals. Little is known about the effects of mineral‐organic associations ( MOA ) on the microbial accessibility of OM in permafrost soils and it is not clear which factors control its temperature sensitivity. In order to investigate if and how permafrost soil OC turnover is affected by mineral controls, the heavy fraction ( HF ) representing mostly MOA was obtained by density fractionation from 27 permafrost soil profiles of the Siberian Arctic. In parallel laboratory incubations, the unfractionated soils (bulk) and their HF were comparatively incubated for 175 days at 5 and 15°C. The HF was equivalent to 70 ± 9% of the bulk CO 2 respiration as compared to a share of 63 ± 1% of bulk OC that was stored in the HF . Significant reduction of OC mineralization was found in all treatments with increasing OC content of the HF ( HF ‐ OC ), clay‐size minerals and Fe or Al oxyhydroxides. Temperature sensitivity (Q10) decreased with increasing soil depth from 2.4 to 1.4 in the bulk soil and from 2.9 to 1.5 in the HF . A concurrent increase in the metal‐to‐ HF ‐ OC ratios with soil depth suggests a stronger bonding of OM to minerals in the subsoil. There, the younger 14 C signature in CO 2 than that of the OC indicates a preferential decomposition of the more recent OM and the existence of a MOA fraction with limited access of OM to decomposers. These results indicate strong mineral controls on the decomposability of OM after permafrost thaw and on its temperature sensitivity. Thus, we here provide evidence that OM temperature sensitivity can be attenuated by MOA in permafrost soils.

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).